Acciones que propician la extensión universitaria desde la clase de Educación Física en las carreras universitarias / Actions that promote university extension from the Physical Education class in university careers - Magaly Modesta Quesada-Miranda; Yanisleydis Ramírez-Molina; Luz Diamela Carbonell-Ramos (Universidad de Camagüey Ignacio Agramonte Loynaz, 2020)
University Extension is essential for the formation of professional education, so be encouraged from all contexts and physical education class is not exempt from it, requires the implementation of action item that was shown during the investigation, they will provide students with the necessary skills for their future profession, through these actions can strengthen the health and moral form of personality traits, as well as the formation of habits and physical, intellectual and spiritual, needed to fulfilling its development throughout human fulfillment. Through the method of observation was diagnosed to determine the actions needed to achieve the goal set was essentially university extension achievement through physical education, the stated goal was accomplished by implementing actions designed, obtaining between the meaningful development of physical education through games.